2006
DOI: 10.1097/01.sla.0000239087.00826.b4
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Markers of Brain Injury and Cognitive Function After Cardiopulmonary Bypass

Abstract: NSE and tau are better associated with NCD and less influenced by cardiotomy suction compared with S-100beta. Inflammatory and oxidative stress is associated with NCD post-CPB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
3
13

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 40 publications
7
73
3
13
Order By: Relevance
“…8) Ramlawi et al reported that serum NSE, one of the five isozymes of the glycolytic enzyme, appears to be another marker of brain injury. 9) NSE has a molecular weight of 78 kDa and is found in large amounts in neurons. 10) Different studies have demonstrated a good correlation between the s-100β protein 11) and NSE 12) levels and the neurocongnitive function, although other studies were unable to find evidence to support the hypothesis that early release of the s-100β protein may reflect short 13) or long-term 14) neurologic injury capable of producing cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…8) Ramlawi et al reported that serum NSE, one of the five isozymes of the glycolytic enzyme, appears to be another marker of brain injury. 9) NSE has a molecular weight of 78 kDa and is found in large amounts in neurons. 10) Different studies have demonstrated a good correlation between the s-100β protein 11) and NSE 12) levels and the neurocongnitive function, although other studies were unable to find evidence to support the hypothesis that early release of the s-100β protein may reflect short 13) or long-term 14) neurologic injury capable of producing cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…isturbed sleep and sleep-wake rhythms represent a major problem for patients after surgery 1 and may result in prolonged postoperative convalescence, 2 cardiovascular morbidity, [3][4][5] cognitive dysfunction, 6,7 and impaired immune function. [8][9][10][11] Furthermore, improved morbidity and mortality has been correlated with a more marked rest-activity rhythm.…”
mentioning
confidence: 99%
“…In patients with ischemic stroke, the release of NSE has been associated with neurological outcomes and infarct volume (17,18,27). Increased NSE level is significant associated with postoperative neurocognitive dysfunction (28).…”
Section: Discussionmentioning
confidence: 99%